New ripiphorid beetles in mid-Cretaceous amber from Myanmar (Coleoptera: Ripiphoridae): First Pelecotominae and possible Mesozoic aggregative behaviour in male Ripidiinae. (31st December 2016) - Batelka, Jan; Prokop, Jakub; Engel, Michael S.
Abstract: New fossil material of ripiphorid beetles (Tenebrionoidea: Ripiphoridae) is described and figured in lowermost Cenomanian amber from the Hukawng Valley of northern Myanmar. Flabellotoma heidiae gen. et sp. nov. is the Mesozoic representative of the putatively primitive subfamily Pelecotominae, represented by an almost completely preserved male. The new genus is compared with all extant members of the subfamily and is most notably distinguishable by an autapomorphic combination of a reduced tibial spur formula and unique ventral abdominal sclerite, and presumably in antennal structure as well. In addition, a syninclusion of eight males of Ripidiinae is discussed. The males are similar to Paleoripiphorus deploegi Perrichot, Nel, et Néraudeau in roughly coeval amber from western France. The syninclusion is interpreted as a result of aggregative behaviour during the flight activity of males, thereby representing the earliest documented evidence of such ethology. Brief remarks are made regarding the similarities among Cretaceous amber beetle faunas, and Mesozoic taxa previously attributed to Ripiphoridae are newly reconsidered.